Influence of Soft Filler on Stress Concentration Factor of Elliptic Holes in a Rectangular Plate - 杨林虎 朱涵 谭党联 (Transactions of Tianjin University, 2012)
Finite element models were established to analyze the influence of soft filler on stress concentration for a rectangular plate with an elliptic hole in the center. The influence was quantified by means of stress concentration fac- tor （SCF）. Seven shape factors of the elliptic hole and three levels of elasticity modulus of the soft filler were consid- ered. The reduction coefficient and sensitivity index of SCF are the two indicators in evaluating the influence of soft filler. It was found that the reduction coefficient of SCF increases significantly as the shape factor and the elasticity modulus of the filler increase, indicating that soft filler can reduce the concentrated stress effectively, especially when the shape factor is great. Analysis for the sensitivity index of SCF indicates that SCF is more sensitive to materials with small elasticity modulus than to materials with large one.